HUBUNGAN MOTIVASI TEMAN SEBAYA DENGAN PERILAKU KONSUMSI BUAH DAN SAYUR PADA MAHASISWA FAKULTAS KEDOKTERAN - rosabella salsa ayu; Efyluk Garianto; Budiarto Adiwinoto; Annisa Ullya Rasyida (Jurnal Kesehatan Masyarakat, 2022)
The phenomenon of dietary habit that is more common among college students currently is fast food, because of its popularity than other types of food. The data showed that the highest level of fast food consumption occurred among students, including university students. This research was aimed at the students of Medical Faculty at Hang Tuah University, Surabaya, because of the tight lecture schedule, often affected the dietary habit and tended to choose foods that were less nutritious. This research aimed at determining the relationship between peer motivation and fruit and vegetable consumption behavior among students of the Medical Faculty 2018, Hang Tuah University, Surabaya. This research applied an observational analytic design through data collection by cross sectional. The numbers of research subjects were 96 students by the sampling technique using purposive sampling. Data collection was conducted by distributing online questionnaires through the jotform website which aimed at the research sample. The data that has been collected showed that the respondent's sense of motivation from peers was classified as sufficient (64.6%), continued well (22.9%) and less (12.5%). The results of the fruit and vegetable consumption behavior of the respondents showed that most of them had a good level (87.5%) and those who were less (12.5%). The data was analyzed by the Spearman`s Rho correlation test. It showed that there was a significant relationship between peer motivation and fruit and vegetable consumption behavior (p = 0.007).